Quantitative analysis and assessment of base composition asymmetry and gene orientation bias in bacterial genomes. Issue 9 (11th April 2019) - Quan, Chun‐Lan; Gao, Feng
Abstract : Base composition asymmetry and gene orientation bias are two common genomic structures in bacterial genomes. Here, correlation coefficients between nucleotide disparities and coding sequence (CDS) skew have been calculated, which provides insights into their relationship from an individual genome perspective. Consequently, we find GC and RY disparities correlate significantly with CDS skew, since around 60% of the bacterial genomes under study have correlation coefficients > 0.9. Then, we present a model for quantitative assessment of nucleotide disparity and CDS skew in which a numerical index R 2 is used for evaluation. We find that skew curves with higher R 2 perform better on the prediction of replication origins in bacteria. Abstract :